2010
DOI: 10.1016/j.ijgo.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomized, placebo‐controlled trial of misoprostol and routine uterotonics for the prevention of postpartum hemorrhage

Abstract: Misoprostol plus routine uterotonics resulted in modest reductions of blood loss in the third stage of labor, but the effects did not reach statistical significance. Larger studies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
6
10
0
Order By: Relevance
“…Shivering and pyrexia were found to be significant adverse effects in the misoprostol group in the present study; again, similar observations have been made in almost all other studies in identical proportions [3][4][5][6][7][8][9][10][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Shivering and pyrexia were found to be significant adverse effects in the misoprostol group in the present study; again, similar observations have been made in almost all other studies in identical proportions [3][4][5][6][7][8][9][10][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…Two recent studies found a diminution of blood loss on the addition of a 400-μg sublingual dose of misoprostol to routine oxytocic use; however, this difference was not significant [21,22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results contrast with findings from trials conducted in Africa evaluating the use of misoprostol as an add-on to routine uterotonics in the prevention of PPH. Both Fawole et al [22] and Hofmeyr et al [7] did not find any significant reduction in the risk of PPH when misoprostol was used as an add-on to routine uterotonics for the prevention of PPH (relative risk [RR] 0.96, 95% CI 0.63–1.45 and RR 0.64; 95% CI, 0.38–1.07 respectively). It is however not uncommon for the results of propensity score adjusted studies to differ from that of randomised controlled trials [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…IJGO, because of its international focus, has recently been able to publish major randomized clinical trials that add to the evidence‐based literature on the gynecologic and obstetric use of misoprostol [7,8], the use of tranexamic acid to prevent and manage postpartum hemorrhage (PPH) [9], and innovative clinical approaches to the management of PPH [10]. In addition, we have published important papers describing clinical programs that can improve outcomes and health through the implementation of evidence‐based practices and interventions [11,12].…”
mentioning
confidence: 99%